2017
DOI: 10.1111/jam.13426
|View full text |Cite
|
Sign up to set email alerts
|

Selection of indigenousLactobacillus paracaseiCD4 andLactobacillus gastricusBTM 7 as probiotic: assessment of traits combined with principal component analysis

Abstract: Milk-based products serve as reservoir for bacterial species with probiotic attributes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
1
8
0
2
Order By: Relevance
“…In this study, the lactobacilli antioxidant capacity was focused on intact cells, cell-free supernatants and intracellular extracts. The important DPPH scavenging rates using cell-free supernatants are consistent with those reported by Sharma et al [43]. Otherwise, the DPPH scavenging activity of intact cells was greater than the rates recorded for the intracellular extracts, as reported in previous studies [70,71].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, the lactobacilli antioxidant capacity was focused on intact cells, cell-free supernatants and intracellular extracts. The important DPPH scavenging rates using cell-free supernatants are consistent with those reported by Sharma et al [43]. Otherwise, the DPPH scavenging activity of intact cells was greater than the rates recorded for the intracellular extracts, as reported in previous studies [70,71].…”
Section: Discussionsupporting
confidence: 91%
“…sakei isolated from kimchi impeded the biofilm formation by a clinical L. monocytogenes strain. Similarly, Mahdi et al [43] showed the potential of a Lb. plantarum strain to prevent the biofilm formation by E. coli strains [52].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…La búsqueda inicial y selección de probióticos implica ensayos de: a) utilización de carbohidratos y proteínas, b) estabilidad fenotípica y genotípica, incluida la estabilidad de los plásmidos, c) detección de resistencia a antibióticos, d) inmunogenicidad, e) inhibición del crecimiento de patógenos y saprófitos, f) producción de bacteriocinas u otras sustancias antimicrobianas g) resistencia al ácido y a sales biliares, h) capacidad para hidrolizar sales biliares e i) existencia de posibles factores de virulencia (Sharma, Mahajan, Attri & Goel, 2017). Otros análisis muy importantes son los de adhesión, que comprenden ensayos de autoagregación, hidrofobicidad superficial, adhesión a mucosas y células intestinales, entre otros.…”
Section: Productos No Lácteos Como Vehículos Para Probióticosunclassified
“…Después de los ensayos in vitro, se realizan ensayos preclínicos con modelos animales y finalmente los ensayos clínicos con humanos (Ranadheera, Baines & Adams, 2010). Este tipo de estudios (in vitro, con modelos animales y en humanos), con los protocolos adecuados, también deben hacerse, para determinar los beneficios que produce la cepa al consumidor (Sharma, Mahajan, Attri & Goel, 2017).…”
Section: Productos No Lácteos Como Vehículos Para Probióticosunclassified